Sustainable Jute-Based Composite Materials Mechanical and Thermomechanical Behaviour - Jabbar, Abdul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book shows how jute waste is collected from industry and used as a cheaper source to extract and use cellulose. Novel environment-friendly methods are explored for surface modification of natural fibers. The advantages of using biocomposites are listed and the author shows how they can be used effectively as secondary structural parts.
Introduction -- Literature Review -- Research Methodology -- Effect of Pulverized Micro Jute Fillers Loading on the Mechanical, Creep and Dynamic Mechanical Properties of Jute/Green Epoxy Composites -- Extraction of Nanocellulose from Waste Jute Fibers and Characterization of Mechanical and Dynamic Mechanical Behavior af Nanocellulose Coated Jute/Green Epoxy Composites -- Flexural, Creep and Dynamic Mechanical Evaluation of Novel Surface Treated Woven Jute/Green Epoxy Composites -- Conclusions and Future Work.
Keywords: Nanotechnology; Ceramic materials; Manufactures; Nanotechnology; Ceramics; Machines, Tools, Processes